The Impact of Preoperative Serum Anti-TNFα Therapy Levels on Early Postoperative Outcomes in Inflammatory Bowel Disease Surgery. Issue 3 (March 2015) - Lau, Cheryl; Dubinsky, Marla; Melmed, Gil; Vasiliauskas, Eric; Berel, Dror; McGovern, Dermot; Ippoliti, Andrew; Shih, David; Targan, Stephan; Fleshner, Phillip
Abstract : Objective: Assess the impact of preoperative serum antitumor necrosis factor-α (anti-TNFα) drug levels on 30-day postoperative morbidity in inflammatory bowel disease (IBD) patients. Background: Studies on the association of anti-TNFα drugs and postoperative outcomes in IBD are conflicting due to variable pharmacokinetics of anti-TNFα drugs. It remains to be seen whether preoperative serum anti-TNFα drug levels correlate with postoperative morbidity. Methods: Thirty-day postoperative outcomes of consecutive IBD surgical patients with serum drawn within 7 days preoperatively were studied. The total serum level of 3 anti-TNFα drugs (infliximab, adalimumab, and certolizumab) was measured, with ≥0.98 μg/mL considered as detected. Data were also reviewed according to a clinical cutoff value of 3 μg/mL. Results: A total of 217 patients [123 with Crohn disease (CD) and 94 with ulcerative colitis (UC)] were analyzed; 75 of 150 (50%) treated with anti-TNFα therapy did not have detected levels at the time of surgery. In the UC cohort, adverse postoperative outcome rates between the undetectable and detectable groups were similar when stratified according to type of UC surgery. In the CD cohort, there was a higher but statistically insignificant rate of adverse outcomes in the detectable versus undetectable groups. Using a cut off level of 3 μg/mL, postoperative morbidity (odds ratio [OR] = 2.5, P = 0.03) and infectious complications (OR = 3.0, P = 0.03) were significantly higher in the ≥3 μg/mL group. There were higher rates of postoperative morbidity ( P = 0.047) and hospital readmissions ( P = 0.04) in the ≥8 μg/mL compared with <3 μg/mL group. Conclusions: Increasing preoperative serum anti-TNFα drug levels are associated with adverse postoperative outcomes in CD but not UC patients. Abstract : The impact of antitumor necrosis factor-α (anti-TNFα) therapy on the postoperative course of inflammatory bowel disease (IBD) is controversial, and many studies' results are conflicting. This study evaluates the association of serum anti-TNFα drug levels with the risk of early postoperative complications in a cohort of patients with IBD.